Accountants as institutional entrepreneurs: changing routines in a telecommunications company. Issue 3 (23rd September 2014) - Sharma, Umesh; Lawrence, Stewart; Lowe, Alan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explicate the role of institutional entrepreneurs who use accounting technology to accomplish change within a privatised telecommunications company. Design/methodology – The case study method is adopted. The authors draw on recent extension to institutional theory that gives greater emphasis to agency including concepts such as embeddedness, institutional entrepreneurs and institutional contradiction. Findings – As part of the consequences of new public management reforms, we illustrate how institutional entrepreneurs de-established an older state-run bureaucratic and engineering-based routine and replaced it with a business- and accounting-based routine. Eventually, new accounting routines were reproduced and taken for granted by telecommunications management and employees. Research Limitations/implications – As this study is limited to a single case study, no generalisation except to theory can be made. There are implications for privatisation of state sector organisations both locally and internationally. Originality/value – The paper makes a contribution to elaborating the role of institutional entrepreneurs as agents of change towards privatisation and how accounting was used as a technology of change.